Peningkatan Prestasi Belajar Bahasa Indonesia Dengan Strategi Pembelajaran Lesson Study Pada Siswa Kelas VII D SMPN 3 Ponorogo - Dhea Vica Nuraini; Panji Kuncoro Hadi; Titik Dwi Astuti (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
The purpose of this study is to be able to describe the improvement of Indonesian language learning achievement with the application of lesson study learning strategies in class VII D students of SMPN 3 Ponorogo in the 2022/2023 academic year. The approach in this research is descriptive qualitative. The process of Classroom Action Research (PTK) was carried out using the model of Kemmis and Mc.Taggart. The research subjects used were students in class VII D SMPN 3 Ponorogo, totalling 32 students. Techniques used for data collection were observation and interview. The lesson study learning strategy for Indonesian language learning material on summarising fiction and non-fiction books was carried out with three stages, namely plan, do, and see which were carried out in three cycles. The results of data obtained the results of learning completeness by students who were classically